1997
DOI: 10.1520/jfs14072j
|View full text |Cite
|
Sign up to set email alerts
|

Possible Markers for Postmortem Drug Redistribution

Abstract: The possibility that postmortem biochemical changes in blood might parallel drug redistribution and thus serve as markers was explored in a detailed case study. Eighteen blood and 14 tissue and fluid samples were taken at autopsy 16 h after the death of a 34-year-old female from amitriptyline overdose. Ranges of drug concentrations in blood were amitriptyline 1.8 to 20.2 μg/mL, nortriptyline 0.6 to 7.3 μg/mL, levels were lowest in femoral vein and highest in pulmonary vein blood. Corresponding levels of 17 ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 15 publications
1
15
0
1
Order By: Relevance
“…On the other hand, the drug level in pericardial fluid, as was illustrated by the example of amitriptyline and nortryptyline, was not much increased. It was up to 2.5 times higher for amitriptyline (in comparison with the drug level in the femoral vein) and in one case even lower for nortryptyline [19,23,36].…”
Section: Drugs For Mood Disordersmentioning
confidence: 80%
See 1 more Smart Citation
“…On the other hand, the drug level in pericardial fluid, as was illustrated by the example of amitriptyline and nortryptyline, was not much increased. It was up to 2.5 times higher for amitriptyline (in comparison with the drug level in the femoral vein) and in one case even lower for nortryptyline [19,23,36].…”
Section: Drugs For Mood Disordersmentioning
confidence: 80%
“…Indeed, the postmortem toxicological data bore that out; the heart of the deceased contained about a 7 times higher concentration than the femoral vein [127]. The extensive tissue distribution of TCAs is in accordance with their high lipophilicity and the large volume of distribution [20,23]. Accumulation of TCAs in the heart was also confirmed by the mean Kp values for amitriptyline (4.6), nortriptyline (7.3), doxepin (3.7), desipramine (4.6) and imipramine (4.3) [8].…”
Section: Drugs For Mood Disordersmentioning
confidence: 90%
“…PMR is one of many factors that may lead to changes in drug concentrations after death. It was first reported by Gee et al [1] and many studies have been performed to prove the occurrence of this phenomenon [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. It was reported that drug concentrations in the body may change according to the time of death, environment, sampling site, volume of distribution, diffusion, redistribution in body cavities and drug metabolism after death [19].…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary work in the late 1990s suggested that five amino acids (methionine, leucine, valine, glycine and serine) showed strong positive correlation to drug concentrations of the tricyclic antidepressant amitriptyline (known to undergo extensive redistribution due to its high volume of distribution) analysed in post-mortem pulmonary blood samples. The results suggested that the amino acids, in particular methionine, may be a suitable marker for redistribution artefact for pulmonary drug shifts 13 . As of yet, a marker for this phenomenon has not been elucidated.…”
Section: Discussionmentioning
confidence: 98%
“…It has now been established and has become common practice, that peripheral blood should be obtained from a femoral vessel 4,12 , yet it remains that the extent of redistribution artefacts is an unknown quantity. Whilst markers for the extent of redistribution have been evaluated 13 it still remains a challenging factor in the interpretation of post-mortem toxicology. Similarly the published reference data has evolved from that reported in serum samples to include whole blood 14 as well as distinguishing from data derived from a single drug to that in combination with alcohol and/or other drugs.…”
Section: Introductionmentioning
confidence: 99%